잇솔질 교육 프로그램이 학령전기 아동의 구강건강에 미치는 효과 - 강복희; 박선남; 송경애; 문정순; Kang, Bok-Hee; Park, Sun-Nam; Sohng, Kyeong-Yae; Moon, Jung-Soon (Journal of Korean Academy of Nursing, 2008)
Purpose: To examine the effect of tooth-brushing education on the oral health of preschoolers. Methods: A quasi-experimental design with a non-equivalent control group was used. Two kindergartens were selected and 39 preschoolers from one kindergarten were assigned to the experimental group with tooth-brushing education and 39 from the other kindergarten to the control group. The tooth-brushing education program included 1 session on oral health education, individual tooth-brushing instruction for 1 week and supervised tooth-brushing after lunch for 4 weeks. Oral health behavior including use of tooth paste, tooth-brushing time and method of tooth-brushing, plague, streptococcus mutans, lactobacillus and dental caries were measured before and after the education. Fisher's exact test, t-test and paired t-test with the Window SAS 9.1 program were used to analyze the data. Results: A significant increase in the use of tooth paste, tooth-brushing time and the practice of correct tooth-brushing and a decrease in plague and development of dental caries were observed in the experimental group. Conclusion: This tooth-brushing education was partially effective in improving oral health of preschoolers.